Analysis of mycotoxins in coffee and risk assessment in Spanish adolescents and adults. (December 2015) - García-Moraleja, A.; Font, G.; Mañes, J.; Ferrer, E.
Abstract: Mycotoxins are toxic compounds produced by fungal secondary metabolism that cause toxicological effects. Coffee is a highly popular beverage that is susceptible to contamination by mycotoxigenic fungi. The aim of the present study was to determine the presence of the following 21 mycotoxins in coffee using liquid chromatography tandem mass spectrometry (LC-MS/MS-IT): aflatoxin B1, B2, G1 and G2 ; ochratoxin A; nivalenol; deoxynivalenol; 3-acetyldeoxynivalenol; 15-acetyldeoxynivalenol; diacetoxyscirpenol; neosolaniol; T-2 and HT-2 toxin; sterigmatocystin; enniatin A, A1, B, and B1 ; beauvericin; and fumonisin B1 and B2 . We aimed to determine differences by coffee process (coffee maker, electrical machine, soluble and traditional Turkish process) and to calculate the estimated daily intake (EDI) and risk assessment of mycotoxins from coffee consumption using deterministic approach at various scenarios of food consumption in Spanish adolescents and adults. The results demonstrate that all studied mycotoxins were detected in samples with mean concentrations ranging from 0.69 µg/kg to 282.89 µg/kg. Eleven percent of samples did not show contamination with legislated mycotoxins. Only 15-acetyldeoxynivalenol, deoxynivalenol, neosolaniol, fumonisin B1, and ochratoxin A exhibited significant differences between methods of coffee brewing. The results show that coffee intake does not represent a potential risk for consumers with respect to individual mycotoxin contamination. Graphical abstract: Highlights: Twenty-one mycotoxins are studied in brewed coffee; they were present in 4–93% of samples. A study of different coffee brews exhibits no significant differences in the reduction of most mycotoxins. The estimated daily intake of mycotoxins exhibits a highly exposed segment of consumers (99th percentile). The risk assessment indicates that coffee consumption is safe with regards to mycotoxin exposure in the mean population.